Performance improvement of organic solar cells with the introduction of branched zinc oxide nanorods. (1st June 2015) - Wei, Fanan; Jiang, Minlin; Zhou, Lei; Dong, Zaili
Abstract : Zinc oxide (ZnO) nanorods with branches are synthesised through facile hydrothermal approach at relatively low temperature. With the prepared ZnO nanostructures as the hole‐blocking layer, organic solar cells based on poly(3‐hexylthiophene): 1‐(3‐methoxycarbonyl)propyl‐1‐phenyl[6, 6]C61 are fabricated. For comparison, devices with planar ZnO thin film and bare ZnO nanorods are manufactured as well. J – V curves show that the best device performance is achieved by the branched nanorod‐based solar cell. Owing to the decreased charge carrier travelling length, the nanorod‐based device shows higher short circuit current ( J sc ) than that of the device with planar ZnO layer. Moreover, the solar cell with branched nanorods shows larger open‐circuit voltage ( V oc ) than that with bare nanorods. Therefore, the performance of organic photovoltaic is enhanced with the introduction of branched ZnO nanorods. Finally, the mechanism of device performance improvement upon the introduction of branched nanorods is discussed.